Subcutaneous sacrococcygeal myxopapillary ependymoma misdiagnosed as pilonidal disease. Issue 1 (2nd January 2020) - Kelly, Aisling; Nally, Deirdre; Crowther, Stephen; Kavanagh, Dara
Abstract : Ependymomas are neoplasms which arise from the radial glial cells, which many recent studies have proposed are neural stem cells. Extracranial ependymomas are rare. We present the case report and supporting multimedia of a 37-year-old man who presented with a painless intergluteal swelling which was diagnosed clinically as a pilonidal cyst. However, on excision, he was found to have a subcutaneous sacrococcygeal myxopapillary ependymoma based on histological findings. His management and follow-up are presented and discussed. Given the rare nature of this condition, there is a lack of published guidelines on management and follow-up protocols. Supporting evidence is limited to sporadic case reports. This case highlights the diagnostic challenges and management strategies adopted supported by the best available evidence.